Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To solve this problem, we need to apply transformations to the initial vertices [tex]\( B(-3, 0), C(2, -1), D(-1, 2) \)[/tex] and see which sequence leads us to [tex]\( B^{\prime \prime}(-2,1), C^{\prime \prime}(3,2), D^{\prime \prime}(0,-1) \)[/tex].
Let's check the options provided step by step.
### Option 1: [tex]\((x, y) \rightarrow (x, -y) \rightarrow (x+1, y+1)\)[/tex]
First Transformation: [tex]\((x, y) \rightarrow (x, -y)\)[/tex]
- [tex]\( B(-3, 0) \rightarrow B'(-3, 0) \)[/tex]
- [tex]\( C(2, -1) \rightarrow C'(2, 1) \)[/tex]
- [tex]\( D(-1, 2) \rightarrow D'(-1, -2) \)[/tex]
Second Transformation: [tex]\((x, y) \rightarrow (x+1, y+1)\)[/tex]
- [tex]\( B'(-3, 0) \rightarrow B^{\prime \prime}(-2, 1) \)[/tex]
- [tex]\( C'(2, 1) \rightarrow C^{\prime \prime}(3, 2) \)[/tex]
- [tex]\( D'(-1, -2) \rightarrow D^{\prime \prime}(0, -1) \)[/tex]
As a result, we obtain the vertices:
- [tex]\( B^{\prime \prime}(-2, 1) \)[/tex]
- [tex]\( C^{\prime \prime}(3, 2) \)[/tex]
- [tex]\( D^{\prime \prime}(0, -1) \)[/tex]
This matches the target vertices. Therefore, Option 1 is the correct transformation sequence.
Given the correct transformation, we do not need to check the rest. But for completeness:
### Option 2: [tex]\((x, y) \rightarrow (-x, y) \rightarrow (x+1, y+1)\)[/tex]
First Transformation: [tex]\((x, y) \rightarrow (-x, y)\)[/tex]
- [tex]\( B(-3, 0) \rightarrow B'(3, 0) \)[/tex]
- [tex]\( C(2, -1) \rightarrow C'(-2, -1) \)[/tex]
- [tex]\( D(-1, 2) \rightarrow D'(1, 2) \)[/tex]
Second Transformation: [tex]\((x, y) \rightarrow (x+1, y+1)\)[/tex]
- [tex]\( B'(3, 0) \rightarrow B^{\prime \prime}(4, 1) \)[/tex]
- [tex]\( C'(-2, -1) \rightarrow C^{\prime \prime}(-1, 0) \)[/tex]
- [tex]\( D'(1, 2) \rightarrow D^{\prime \prime}(2, 3) \)[/tex]
These vertices do not match the target vertices.
### Option 3: [tex]\((x, y) \rightarrow (x, -y) \rightarrow (x+2, y+2)\)[/tex]
First Transformation: [tex]\((x, y) \rightarrow (x, -y)\)[/tex]
- [tex]\( B(-3, 0) \rightarrow B'(-3, 0) \)[/tex]
- [tex]\( C(2, -1) \rightarrow C'(2, 1) \)[/tex]
- [tex]\( D(-1, 2) \rightarrow D'(-1, -2) \)[/tex]
Second Transformation: [tex]\((x, y) \rightarrow (x+2, y+2)\)[/tex]
- [tex]\( B'(-3, 0) \rightarrow B^{\prime \prime}(-1, 2) \)[/tex]
- [tex]\( C'(2, 1) \rightarrow C^{\prime \prime}(4, 3) \)[/tex]
- [tex]\( D'(-1, -2) \rightarrow D^{\prime \prime}(1, 0) \)[/tex]
These vertices do not match the target vertices.
### Option 4: [tex]\((x, y) \rightarrow (-x, y) \rightarrow (x+2, y+2)\)[/tex]
First Transformation: [tex]\((x, y) \rightarrow (-x, y)\)[/tex]
- [tex]\( B(-3, 0) \rightarrow B'(3, 0) \)[/tex]
- [tex]\( C(2, -1) \rightarrow C'(-2, -1) \)[/tex]
- [tex]\( D(-1, 2) \rightarrow D'(1, 2) \)[/tex]
Second Transformation: [tex]\((x, y) \rightarrow (x+2, y+2)\)[/tex]
- [tex]\( B'(3, 0) \rightarrow B^{\prime \prime}(5, 2) \)[/tex]
- [tex]\( C'(-2, -1) \rightarrow C^{\prime \prime}(0, 1) \)[/tex]
- [tex]\( D'(1, 2) \rightarrow D^{\prime \prime}(3, 4) \)[/tex]
These vertices do not match the target vertices.
Therefore, the correct sequence of transformations to achieve the desired vertices is:
Option 1: [tex]\((x, y) \rightarrow (x, -y) \rightarrow (x+1, y+1)\)[/tex]
Let's check the options provided step by step.
### Option 1: [tex]\((x, y) \rightarrow (x, -y) \rightarrow (x+1, y+1)\)[/tex]
First Transformation: [tex]\((x, y) \rightarrow (x, -y)\)[/tex]
- [tex]\( B(-3, 0) \rightarrow B'(-3, 0) \)[/tex]
- [tex]\( C(2, -1) \rightarrow C'(2, 1) \)[/tex]
- [tex]\( D(-1, 2) \rightarrow D'(-1, -2) \)[/tex]
Second Transformation: [tex]\((x, y) \rightarrow (x+1, y+1)\)[/tex]
- [tex]\( B'(-3, 0) \rightarrow B^{\prime \prime}(-2, 1) \)[/tex]
- [tex]\( C'(2, 1) \rightarrow C^{\prime \prime}(3, 2) \)[/tex]
- [tex]\( D'(-1, -2) \rightarrow D^{\prime \prime}(0, -1) \)[/tex]
As a result, we obtain the vertices:
- [tex]\( B^{\prime \prime}(-2, 1) \)[/tex]
- [tex]\( C^{\prime \prime}(3, 2) \)[/tex]
- [tex]\( D^{\prime \prime}(0, -1) \)[/tex]
This matches the target vertices. Therefore, Option 1 is the correct transformation sequence.
Given the correct transformation, we do not need to check the rest. But for completeness:
### Option 2: [tex]\((x, y) \rightarrow (-x, y) \rightarrow (x+1, y+1)\)[/tex]
First Transformation: [tex]\((x, y) \rightarrow (-x, y)\)[/tex]
- [tex]\( B(-3, 0) \rightarrow B'(3, 0) \)[/tex]
- [tex]\( C(2, -1) \rightarrow C'(-2, -1) \)[/tex]
- [tex]\( D(-1, 2) \rightarrow D'(1, 2) \)[/tex]
Second Transformation: [tex]\((x, y) \rightarrow (x+1, y+1)\)[/tex]
- [tex]\( B'(3, 0) \rightarrow B^{\prime \prime}(4, 1) \)[/tex]
- [tex]\( C'(-2, -1) \rightarrow C^{\prime \prime}(-1, 0) \)[/tex]
- [tex]\( D'(1, 2) \rightarrow D^{\prime \prime}(2, 3) \)[/tex]
These vertices do not match the target vertices.
### Option 3: [tex]\((x, y) \rightarrow (x, -y) \rightarrow (x+2, y+2)\)[/tex]
First Transformation: [tex]\((x, y) \rightarrow (x, -y)\)[/tex]
- [tex]\( B(-3, 0) \rightarrow B'(-3, 0) \)[/tex]
- [tex]\( C(2, -1) \rightarrow C'(2, 1) \)[/tex]
- [tex]\( D(-1, 2) \rightarrow D'(-1, -2) \)[/tex]
Second Transformation: [tex]\((x, y) \rightarrow (x+2, y+2)\)[/tex]
- [tex]\( B'(-3, 0) \rightarrow B^{\prime \prime}(-1, 2) \)[/tex]
- [tex]\( C'(2, 1) \rightarrow C^{\prime \prime}(4, 3) \)[/tex]
- [tex]\( D'(-1, -2) \rightarrow D^{\prime \prime}(1, 0) \)[/tex]
These vertices do not match the target vertices.
### Option 4: [tex]\((x, y) \rightarrow (-x, y) \rightarrow (x+2, y+2)\)[/tex]
First Transformation: [tex]\((x, y) \rightarrow (-x, y)\)[/tex]
- [tex]\( B(-3, 0) \rightarrow B'(3, 0) \)[/tex]
- [tex]\( C(2, -1) \rightarrow C'(-2, -1) \)[/tex]
- [tex]\( D(-1, 2) \rightarrow D'(1, 2) \)[/tex]
Second Transformation: [tex]\((x, y) \rightarrow (x+2, y+2)\)[/tex]
- [tex]\( B'(3, 0) \rightarrow B^{\prime \prime}(5, 2) \)[/tex]
- [tex]\( C'(-2, -1) \rightarrow C^{\prime \prime}(0, 1) \)[/tex]
- [tex]\( D'(1, 2) \rightarrow D^{\prime \prime}(3, 4) \)[/tex]
These vertices do not match the target vertices.
Therefore, the correct sequence of transformations to achieve the desired vertices is:
Option 1: [tex]\((x, y) \rightarrow (x, -y) \rightarrow (x+1, y+1)\)[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.